Respuesta :
Answer:
Therefore, x = 1 and y = -1 .
Step-by-step explanation:
The steps are :
[tex]4x - 5y = 9 - - - (1)[/tex]
[tex] - 6x + 5y = - 11 - - - (2)[/tex]
[tex](1) + (2)[/tex]
[tex]4x + ( - 6x) = 9 + ( - 11)[/tex]
[tex] - 2x = - 2[/tex]
[tex]x = 1[/tex]
[tex]sub \: x = 1 \: into \: (2)[/tex]
[tex](2)⇒[/tex]
[tex] - 6(1) + 5y = - 11[/tex]
[tex] - 6 + 5y = - 11[/tex]
[tex]5y = - 11 + 6[/tex]
[tex]5y = -5[/tex]
[tex]y = -1 [/tex]
Answer:
I hope it work
Step-by-step explanation:
- 4x-5y=9
- -6x+5y=-11
adding both the equations
4x-5y=9
-6x+5y=-11
-2x+0y=-2
-2x=-2
Now divide both sides by -2
-2/-2 x= -2/-2